Comparison of Dexmedetomidine and Labetalol for Attenuating Stress Response in Hypertensive Patients: Dexmedetomidine and Labetalol for Attenuating Stress Response in Hypertensive Patients - Khalid, Rootaba; Afzal, Farrukh; Nayyar, Shaheer; Tariq, Sumayya; Ashfaq, Shumaila; Sabir, Sara; Feroze, Rehana (Pakistan Journal of Health Sciences, 2026)
Laryngoscopy and tracheal intubation during general anesthesia provoke a sympathetic stress reaction that has significant hemodynamic changes. This can be risky, particularly in patients with controlled hypertension with compromised cardiovascular reserve. Objective: To compare the effect of dexmedetomidine and labetalol for attenuating stress response in hypertensive patients. Methods: A quasi-experimental study that involved 200 controlled hypertensive patients admitted to the elective surgery and placed under general anesthetic procedures. Patients received Intravenous dexmedetomidine (0.1 mcg/kg) or labetalol (0.1 mg/kg). It was observed that the mean heart rate and mean arterial blood pressure were measured at baseline and two minutes after endotracheal intubation. The statistics were performed using the independent sample t-test, which was used to compare the results observed between the two treatment groups. Results: The heart rate 2 minutes following intubation was much lower in Group D (78 ± 8.27 beats/minute) than in Group L (81 ± 5.30 beats/minute, p=0.0026). Further, the mean arterial blood pressure was declining remarkably in the dexmedetomidine group (98 ± 7.26 mmHg), compared to the labetalol group (101 ± 8.2 mmHg; p=0.0067). Conclusions: The present group of controlled hypertensive patients indicated that dexmedetomidine pre-induction, in comparison to labetalol, led to a significantly more significant reduction of hypertensive and tachycardic reaction to laryngoscopy and endotracheal intubation.